Improving the uptake of prehabilitation interventions for older adults prior to cancer treatment using telehealth in the Geriatric Oncology One-Stop Clinic. Issue 28 (1st October 2022) - Ng, Yean Shin; Said, Noorhanah Mohd; Chen, Matthew Zhixuan; Eng, Wan Nghee; Ling, Natalie Mun Wai; Low, Jia Li; Yao, Yao; Loy, Yijun; Chun, Meiling; Wong, Wei Yee; Ong, Jie Xin; Luah, Vivian; et al.
Abstract : 55 Background: Prehabilitation in older patients aged ≥ 65 years undergoing cancer surgery and systemic therapy is crucial in reducing treatment complications and improving physical health, psychological well-being, quality of life (QOL) and cancer-related outcomes. However, a majority of older patients (80%) attending our Geriatric Oncology (GO) One-Stop clinic do not receive same day Comprehensive Geriatric Assessment (CGA)-directed Allied Health Interventions (AHI) for prehabilitation during their First Visit (FV). Objectives: The objective of this study is to increase the uptake of same day CGA-directed AHI for prehabilitation from 20% to 60% using telehealth. Methods: Older patients planned for an FV at the GO One-Stop clinic in an academic tertiary center, the National University Cancer Institute, Singapore (NCIS) were recruited. Our workflow was revised so that all FV patients underwent CGA via telehealth prior to the physical visit. Based on the preliminary CGA findings, a multidisciplinary geriatric oncology board planned for prehabilitation interventions which would be performed on the same day as the physical visit. Interim follow-up via telehealth by GO nurses helped to monitor patients for treatment-related toxicities and development of new geriatric syndromes. QOL was assessed during the FV and 3 months later. Results: Two hundred seventy-five patients were recruited from July 2020 to January 2022. 60% (n = 165) received prehabilitation interventions in the One-Stop clinic. The average time spent per visit was shortened from 4 hours to 2.5hours, but completed interventions on same day rose from 1 to 3. The proportion of patients who responded that they benefited from the program on the patient satisfactory survey remained high at 96%. 84.8% were satisfied with the hybrid telehealth model and 80.8% of them reported a maintained or improved QOL after being enrolled into the program. Conclusions: Adoption of telehealth for CGA is a feasible and effective method in improving prehabilitation interventions uptake for GO patients. GO hybrid model of care is a sustainable practice with no additional cost incurred.